PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PKn BAGI SISWA SD KELAS V - Zein Situmeang, Farid Zaki; Darwis, Umar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research conducted aims to determine the effect of the use of comic media on increasing students' interest in learning PKn subjects for grade V elementary school students. This research is a quantitative approach using an experimental method. From the results of the research conducted, it is known that the use of comic media in PKn learning has a significant effect on the learning outcomes of grade V students of DN 060818 Medan. This can be seen from the t-count value of 3.498 and T_table 1.72. The Sig. (2-tailed) value <0.001, meaning <0.05. Because t_count> from t_table, H0 is rejected and Ha is accepted, which means that there is an effect of the use of comic media on increasing students' interest in learning in grade V of SDN 060818 Medan. The average difference between the two groups is 13.700 with a statistically significant difference, and the 95% confidence interval range is between 5.748 and 21.652. This shows that there is a significant difference between the two groups of classes being compared, namely the control and experimental classes.